Dynamic Electromagnetic Control Technology and Its Application Based on Metasurface - Yuxi LI; Ruichao ZHU; Sai SUI; Yuxiang JIA; Chang DING; Yajuan HAN; Shaobo QU; Jiafu WANG (Leida xuebao)
Electromagnetic (EM) metasurfaces are a novel type of artificial EM material exhibiting great advantages for wireless communication and signal processing. By introducing external excitation (mechanical, thermal, electrical, optical, and magnetic excitations), the EM metasurface realizes a more flexible dynamic control of the EM response. On the basis of the dynamic control method, the EM metasurface can accurately control the phase, amplitude, polarization mode, propagation mode, and other characteristics of EM waves to realize wavefront control in different application scenarios. In this paper, we first summarize the research progress of dynamic control technology for EM metasurfaces. Then, the research status of EM metasurfaces in the fields of holographic imaging, polarization conversion, metalensing, beam steering, and intelligent systems based on the application scenarios is discussed. Finally, the development modes of EM metasurfaces and the development trends of intelligent control in the future are summarized and explored.